2013
DOI: 10.1117/1.oe.52.2.023002
|View full text |Cite
|
Sign up to set email alerts
|

Improving light-emitting diode performance through sapphire substrate double-side patterning

Abstract: Abstract. Here, we present a new double-side patterned sapphire substrate methodology that improves the efficiency of gallium nitride-light emitting diodes (GaN-LEDs). The light extraction efficiency of GaNbased LEDs was analyzed through the use of a ray-tracing simulation. The extraction efficiency was simulated using patterned sapphire substrate LEDs with a variety of shapes, depths, sizes, and spacing. Through the optimal patterning of the various factors, high extraction efficiency was realized and subsequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 11 publications
(14 reference statements)
0
6
0
Order By: Relevance
“…We highlight that the impact of designed outcoupling structures becomes more significant in absorptive LED devices (e.g., InGaN/GaN LEDs with a high fraction of the In composition) . Previous reports have shown that for PSS LED devices cone patterns provide more efficient light extraction and improved GaN crystallinity as compared to hemisphere patterns. Therefore, we postulate that even larger wall-plug efficiency could be obtained in CES LEDs that incorporate cone patterns. Additionally, the inner air cavities in the CES pattern help release the stress accumulated during the heteroepitaxial growth of GaN layers on the sapphire substrate, which leads to reduced wafer bow (Supporting Information Figure S7) .…”
mentioning
confidence: 75%
“…We highlight that the impact of designed outcoupling structures becomes more significant in absorptive LED devices (e.g., InGaN/GaN LEDs with a high fraction of the In composition) . Previous reports have shown that for PSS LED devices cone patterns provide more efficient light extraction and improved GaN crystallinity as compared to hemisphere patterns. Therefore, we postulate that even larger wall-plug efficiency could be obtained in CES LEDs that incorporate cone patterns. Additionally, the inner air cavities in the CES pattern help release the stress accumulated during the heteroepitaxial growth of GaN layers on the sapphire substrate, which leads to reduced wafer bow (Supporting Information Figure S7) .…”
mentioning
confidence: 75%
“…Parabolic nanostructures were manufactured on the PMMA surface by depositing silicon dioxide (SiO 2 ) via a thermal oxidation process. In a subsequent process, the nanostructured surface was further modified via high-density plasma chemical vapor deposition using SiO 2 (Novellus Co., Canada), and thermal nanoimprint lithography was conducted on the PMMA film (Obducat, Sweden) . All stamps were coated with an antisticking layer (Optool DSX, Daikin Chemicals) for the subsequent demolding process …”
Section: Methodsmentioning
confidence: 99%
“…In a subsequent process, the nanostructured surface was further modified via high-density plasma chemical vapor deposition using SiO 2 (Novellus Co., Canada), and thermal nanoimprint lithography was conducted on the PMMA film (Obducat, Sweden). 14 All stamps were coated with an antisticking layer (Optool DSX, Daikin Chemicals) for the subsequent demolding process. 15 Characterization of the Imprinted Surface.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…7(a) and (b). This is because the concave cones are beneficial for the escape of light with middle emission angles, which results from the inclined surface that reduces the incident angles for this light [22], [46], [47]. However, the rougher surface can more significantly decrease the transmittance of light with small incident angles because of the stronger backward scattering, as shown in Fig.…”
Section: Light-extraction Mechanisms Of Msparmmentioning
confidence: 99%